2023
DOI: 10.3390/cancers15030604
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Breast Cancer-Screening Adherence in Vulnerable Populations

Abstract: Breast cancer screening through periodic mammography has been effective in decreasing mortality and reducing the impact of this disease. However, adherence to screening does not meet the desired expectations from all populations. The main objective of this review is to explore the barriers that affect adherence to breast cancer–screening programs in vulnerable populations according to race and/or ethnicity in order to propose measures to reduce the lack of adherence. We conducted a search of publications in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Ponce-Blandón et al highlighted the challenges faced by healthcare workers in handling cultural differences and suggested strategies to educate them about diversity and respect [28]. Ensuring medical confidence in healthcare professionals and systems is crucial for strengthening doctor-patient interactions, increasing satisfaction and adherence to screening, and emphasizing diversity and cultural integration [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ponce-Blandón et al highlighted the challenges faced by healthcare workers in handling cultural differences and suggested strategies to educate them about diversity and respect [28]. Ensuring medical confidence in healthcare professionals and systems is crucial for strengthening doctor-patient interactions, increasing satisfaction and adherence to screening, and emphasizing diversity and cultural integration [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Serral et al emphasized the importance of educating the population, especially susceptible women, about the benefits and risks of breast cancer screening programs so that they could make informed decisions [ 26 ]. Furthermore, to minimize adherence to screening programs, it is advised that women who often ignore screening get yearly health checkups [ 27 ]. Collaborating with healthcare providers is critical for enrolling individuals who satisfy eligibility requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter was similarly identified as a barrier within breast cancer screening in vulnerable populations. 43 In Denmark, Estonia, France, Italy and Portugal, which have higher GDP, the common barriers are related to providers’ insufficient cultural and relational competencies in encounters with vulnerable women. According to McCormack et al , 44 the need to integrate person-centred approach in healthcare has long been recognised.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to optimal implementation and support of these screening programs in the primary care setting are well-documented. [21][22][23] Evidence suggests that PCPs generally feel inadequately supported by staff and electronic systems while feeling uncertain about their responsibility, with less than half of surveyed PCPs reporting that they were very satisfied with the process of managing abnormal screening results for any cancer type. 24 A recent survey revealed that an overwhelming majority of PCPs support patient participation in MCED clinical trials while the majority also have concerns related to management of positive results.…”
Section: Clinical Implications Of Mced Testingmentioning
confidence: 99%